Severe Osteomalacia Related to Long-Term Intravenous Drug Abuse - Leslie Gamache MD; Mark R. Burge MD (SAGE Publishing, 2014)
Objective . We present the clinical, biochemical, and imaging findings of a woman with vitamin D deficiency and severe osteomalacia related to intravenous heroin addiction. Results . A 54-year-old woman with a medical history significant for long-standing heroin abuse presented with complaints of bone pain, muscle cramping, and a left hip ulcer. She had been bed bound for approximately 1 year secondary to pain of uncertain etiology, and her husband was bringing her both food and drugs. She was admitted to the hospital for debridement of a right ischial ulcer. Further workup revealed osteomyelitis of the left hip and severe vitamin D deficiency. Radiologic evaluation demonstrated diffuse osteopenia with pseudofractures, as well as true fractures. Conclusion . This is the first case reported in the English literature of advanced osteomalacia resulting from a debilitating narcotic dependency. Vitamin D deficiency should be considered in patients with poor nutrition and prolonged sunlight deprivation from any cause.